Creating a Canva-Based Approach for Teaching Narrative Text - Rani Nurhaliza; Slamet Wahyudi Yulianto; Noni Trisna Putri; Muhammad Anjar Nugraha (Ma'soem University, 2026)
Narrative text is an important part of English learning at the junior high school level because it helps students develop their reading, writing, and storyline skills. However, many students have difficulty understanding the structure of the text, the flow of events, and complex linguistic elements, while conventional learning approaches are often unable to accommodate students' needs optimally. This creates a gap between theoretical learning approaches and less interesting and less effective classroom learning practices. This study aims to describe the use of Canva as a creative medium in learning narrative text in junior high school. Canva was chosen because it has attractive and interactive visual elements that are believed to improve students' understanding. This study uses a qualitative descriptive method with data collection techniques in the form of classroom observations and semi-structured questionnaires and involves 10 junior high school students as participants. The results showed the use of Canva had a positive impact on students' understanding of the structure of narrative text, such as orientation, complication, resolution, and reorientation. Attractive visuals, such as images and layouts, also increase students' enthusiasm and creativity in the learning process. Thus, the use of Canva has proven effective in bridging the gap between theory and practice and making learning narrative text more enjoyable and meaningful for junior high school students.